Treatment of Mengovirus Infection in Mice with Statolon - Pindak, Frank F. (1967)
A single intraperitoneal injection of statolon was shown to exert a therapeutic effect on mice previously injected with the large plaque-forming variant of mengovirus. The ld(50) and survival time data demonstrated that such treatment was effective when given 2 to 48 hr after infection. No protective effect was apparent when statolon was administered 3, 4, or 5 days after the viral challenge. It was concluded that statolon, or other similar interferon inducers, may be of therapeutic value in instances of accidental or other known exposure to hazardous viral agents.